Microstructure of Polymer Composite Materials - Kalova, Martina; Rusnakova, Sona (Manufacturing Technology Journal, 2017)
This paper deals with problems connected with defects in polymer composite materials and the causes of their occurrences. The microstructure of polymeric materials with carbon and hybrid (carbon / aramid) reinforcement with an epoxy matrix is examined. The evaluation of the microstructures of the two types of composites was performed with the aid of a scanning electron microscope, as well as a 3D light microscope. Defects (dry spots, bubbles, pores,…) in the structure of the material significantly affect its properties, and the question of their elimination is also considered. In order to achieve the most favourable physical and mechanical properties, the production method for the composite materials is important. While preparing test samples, it was used manual lamination technology, where 45% volume fraction of fibre reinforcement could be achieved in the technological regularities.
Keywords: Polymer Composites; Carbon Fiber; Hybrid Fiber; Microstructure